ETIKA MURID TERHADAP GURU DALAM KITAB AL-MANHAJ AS-SAWI KARYA HABIB ZAIN BIN IBRAHIM AL-HUSAINI - Abdul Kadir; Siti Rahmawati (ADDABANA: Jurnal Pendidikan Agama Islam, 2019)
This research is motivated by the thought that the student's ethics towards the teacher is the key to learning success. Therefore, it is necessary to research how the student ethics of the teachers according to Habib Zain ibn Ibrahim al-Husaini's book Al-Manhaj as-Sawi. The subject matter is: How is the student's ethics to the teacher according to Habib Zain bin Ibrahim al-Husaini's book Al-Manhaj as-Sawi? The research is a literature research study. The object is an ethical disciple of teachers according to the book Al-Manhaj as-Sawi by Habib Zain bin Ibrahim al-Husaini. The Data is collected by the technique of literature survey and is processed by editing techniques, coding, and description. Further analyzed by content Analyizys. From the results of research and analysis, it is revealed that the student ethics of the teacher according to Habib Zain al-Husaini in Al-Manhaj as-Sawi is to honor the teacher and his family as the teacher needs, serving him. No impolite attitude toward the teacher, such as sticking his legs at him, eating and drinking before him, because that attitude can make him dislike. Do not precede the teacher on what it wants, i.e. ask permission and blessing the teacher first before acting. Being Tawadhu ' before him by not feeling smarter and denied his opinion. If the teacher walks, then the student must also walk, not drive a vehicle, unless asked for permission or allowed by the teacher to drive. Always pray for the teachers, because praying for the teacher is the same as praying for the parents. In addition, it also respects the sciences (people of science), even though he has never learned (to learn) with him. Keywords: ethics, Al-Manhaj As-Sawi, Habib Zain bin Ibrahim Al-Husaini